Trends Patterns and Emerging Topics in Influencer Marketing a Bibliometric - Loso Judijanto; Andriya Risdwiyanto (Sciences du Nord Economics and Business, 2025)
Influencer marketing has become a central strategy in digital marketing, driven by the rapid growth of social media platforms and changing consumer behavior. As academic interest in this domain has expanded significantly, a systematic understanding of the intellectual structure, research trends, and emerging themes remains essential. This study aims to map the evolution of influencer marketing research by conducting a bibliometric analysis of scholarly publications indexed in the Scopus database. Using VOSviewer, the study examines publication trends, co-authorship networks, country and institutional collaborations, and keyword co-occurrence patterns to identify dominant research streams and emerging topics. The findings reveal that influencer marketing research is strongly anchored in social media and consumer behavior studies, with trust, credibility, engagement, and purchase intention forming the core conceptual foundations. More recent research trends indicate a growing emphasis on strategic and performance-oriented outcomes, platform-specific dynamics, and technological innovations such as machine learning and immersive media. By providing a comprehensive mapping of the field, this study contributes to theoretical consolidation and offers practical insights for researchers and practitioners seeking to understand and advance influencer marketing in an evolving digital ecosystem.